PERLINDUNGAN HUKUM BAGI KONSUMEN PADA PEMBATALAN KONSER MUSIK: STUDI KASUS KONSER MUSIK RASOUNDFEST: Legal Protection For Consumer In The Cancellation Of Musik Concerts: A Case Study Of Rasoundfest Musik Concert - Izaz Alhady; Dian Purnamasari (Reformasi Hukum Trisakti, 2025)
Currently, musik concerts are one of the business fields favored by Indonesian business actors. One example is the Rasoundfest musik concert in Purwakarta. Several parties involved include promoters who act as business actors and ticket buyers who act as consumers. However, in its implementation it did not go as planned. This is due to unfulfilled consumer rights based on Article 4 letters b, e, and h of the UUPK. The problem in this study is what form of legal protection and settlement efforts can consumers make in organizing musik concerts based on the UUPK. This writing uses a normative research method sourced from secondary data and uses primary data. Conclusions are drawn using the deductive method. The result and conclusion on research: Consumers still do not receive full legal protection due to the cancellation of the Rasoundfest musik concert. Consumers should have obtained rights based on Article 4 letters b, e, and h of the UUPK. Then, the settlement efforts that have been made so far by consumers of the Rasoundfest musik concert have only been to the stage of complaining to the organizers. Consumers should be able to make settlement efforts that have been regulated based on the UUPK.